BrAPI - an application programming interface for plant breeding applications - Selby, Peter; Abbeloos, Rafael; Backlund, Jan Erik; Basterrechea Salido, Martin; Bauchet, Guillaume; Benites-Alfaro, Omar E; Birkett, Clay; Calaminos, Viana C; Carceller, Pierre; Cornut, Guillaume; Vasques Costa, Bruno; Edwards, Jeremy D; et al. (Oxford University Press, 2019)
Modern genomic breeding methods rely heavily on very large amounts of phenotyping and genotyping data, presenting new challenges in effective data management and integration. Recently, the size and complexity of datasets have increased significantly, with the result that data is often stored on multiple systems. As analyses of interest increasingly require aggregation of datasets from diverse sources, data exchange between disparate systems becomes a challenge. RESULTS: